Assessment of pediatric cricopharyngeal achalasia with high resolution manometry - Özlem Boybeyi Türer; Numan Demir; Thomas Ciecieraga; Rıza Önder Günaydın; Tutku Soyer (The Turkish Journal of Pediatrics)
Cricopharyngeal achalasia (CPA) is an uncommon cause of oropharyngeal dysphagia (OPD) which is the failure of upper esophageal sphincter (UES) to relax during bolus passage. The diagnostic challenges in OPD have been overcome with the use of high resolution manometry (HRM) in children where a catheter based biomechanical evaluation testing of the oropharyngeal swallowing is performed. Herein, we present a case with severe dysphagia diagnosed as CPA utilizing HRM testing. An 8-year-old boy was seen in our clinic with a two-year history of difficult swallowing, recurrent respiratory tract infections, hypoxia and seizure secondary to aspiration. Esophagography revealed an indentation of the cricopharangeal muscle (CPM) in the cervical part of the esophagus. Videofluroscopic swallow studies (VFSS) revealed cricopharyngeal bar at level of C5-6 and diffuse dysmotility in esophagus. Conventional esophageal manometry revealed absence of peristaltic activity throughout the esophagus. Esophagogastroduodenoscopy revealed narrowing in upper esophagus that with applied force allowed passage of the endoscope. The patient underwent UES dilatation 6 times. He had temporary relief of symptoms. Since he did not have sustained response to dilatation, a botulinium toxin (5IU/each quadrant) injection (BTI) to CPM was performed twice. His symptoms recurred at the end of 3 months. HRM was performed revealing weakness of CPM and uncoordinated contractions and relaxations in UES. We could not reliably differentiate if HRM findings were a sign of primary illness or secondary to BTI. Swallowing rehabilitation was adjusted based on HRM findings. He is still under follow-up with mild dysphagia to certain solids. CPA is an uncommon cause of dysphagia with limited therapeutic options. HRM should be performed in OPD before considering any treatment modality including esophageal dilatation and BTI. HRM has become gold standard diagnostic tool in OPD that provides objective evaluation of pharyngeal and UES motility in children.